The strange case of Dr Jekyll and Mr Hyde and other tales of terror - Stevenson, Robert Louis; Mighall, Robert (Penguin classics, 2002)
"Published as a 'shilling shocker', Robert Louis Stevenson's dark psychological fantasy gave birth to the idea of the split personality. The story of respectable Dr Jekyll's strange association with 'damnable young man' Edward Hyde; the hunt through fog-bound London for a killer; and the final revelation of Hyde's true identity is a chilling exploration of humanity's basest capacity for evil. The other stories in this volume also testify to Stevenson's inventiveness within the gothic genre: 'Olalla', a tale of vampirism and tainted family blood, and 'The Body Snatcher', a gruesome fictionalization of the exploits of the notorious Burke and Hare. This edition contains a critical introduction by Robert Mighall, which discusses class, criminality and the significance of the story's London setting. It also includes an essay on the scientific contexts of the novel and the development of the idea of the 'Jekyll-and-Hyde' personality." -- (Back Cover)
Keywords: Good and evil : Fiction; Horror tales; Multiple personality : Fiction; Physicians : Fiction; Self-experimentation in medicine : Fiction; Antisocial Personality Disorder : Fictional Works; Medicine in Literature; Mental Disorders : Fictional Works; muodonvaihdos; metamorfos (biologi); London (England) : Fiction; Iso-Britannia; Lontoo; Storbritannien; London